A Frequency and Polarization Reconfigurable Dual-Patch Microstrip Antenna for Wireless ISM Band - Cong Danh Bui; Thanh Cuong Dang; Minh Thuan Doan; Truong Khang Nguyen (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This paper proposes a reconfigurable microstrip patch antenna design for wireless ISM band applications. The antenna simultaneously uses PIN Diodes to switch between linear and circular polarization at 2.45 GHz and uses Varactor Diode to continuously tune the operating frequency from 1.73 GHz to 2.45 GHz. The antenna performance is characterized as a combination of ON/OFF state of PIN Diode and a bias voltage of Varactor Diode varying from 0.8V to 10V. A good agreement between simulation and measurement is obtained which validates the proposed method. The proposed frequency/polarization reconfigurable antenna is promising for various applications in wireless ISM band such as DCS (1710 – 1880 MHz), PCS (1850 – 1990 MHz), GSM 1800, GSM 1900, UMTS (1920 – 2170 MHz) and WiFi/Bluetooth (2.4 – 2.5 GHz).